MODEL PENGEMBANGAN PENDIDIKAN ISLAM DI MADRASAH DINIYAH AL-IKHLAS MENONGO SUKODADI LAMONGAN - Manan, Abdul; Maftukhin, Maftukhin (Universitas Islam Lamongan, 2017)
This thesis is the result of field research to determine the educational background that shows how many Diniyah Madrasah Madrasah Diniyah that is untouched by the development of Islamic education in accordance with the times. Diniyah Madrasah Al-Ikhlas Menongo Sukodadi Lamongan is one of Madrasah education Diniyah applying Diniyah Madrasah education development. Educational institutions Madrasah Al-Ikhlas Diniyah Menongo Sukodadi Lamongan imparting education is loaded with style Diniyah Madrasah education schools and combined with the times. The purpose of this study was to determine how the Islamic education development model developed at Madrasah Al-Ikhlas Diniyah and how factors supporting and inhibiting the development model of Islamic education in Madrasah Al-Ikhlas Diniyah. To find out the issues and get clear data, here the author uses qualitative descriptive. Data collection techniques and information is done through observation, interviews and documentar. The results showed that the model of development of Islamic education in Madrasah Al-Ikhlas Diniyah is to use three kinds of models, the first model of synergy between schools, communities and families. Second, the model curriculum that is structured and programmed in accordance with their respective levels. Third, the model oriented Tsaqafah formation of Islam, the Islamic personality and mastery of science. The advice given in this study is the Madrasah Al-Ikhlas Diniyah Menongo Sukodadi Lamongan, in order to improve the quality of development model senantisa Islamic education to integrate into daily activities. Diniyah Madrasah Al-Ikhlas Menongo Sukodadi Lamongan as one Madrasah Diniyah who develop Islamic education models continue to innovate and keep abreast of the times, but still adhere to the principles of Islam.Keywords: Development of Islamic Education